New and little-known mute Trigonidiinae species from China (Orthoptera: Grylloidea: Trigonidiidae) - Li, Shi-Yu; Liu, Yi-Jiao; He, Zhu-Qing (Zootaxa, 2022)
We provide a key to mute Trigonidiinae species from China, and provide morphological features of some nondescript species in brown color. We established a new genus, Zilingxi He gen. nov. with two new species Z. danmai He sp. nov. and Z. dian He sp. nov. from China. The new genus possesses a black line above clypeus; pseudepiphallic paramere of male genitalia possessing 2–3 branches; ovipositor shorter than other genera. Two new species are very similar in morphology, but different in the color pattern in frontal rostrum, and the shape of male genitalia. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).